Implementasi Teori Humanistik Dalam Meningkatkan Kesehatan Mental - Hasanah, Wahdah Oktafia; Haziz, Fara Tiara (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2021)
Mental health is very important in our lives as humans. However, sometimes many people waste their mental health on themselves and don’t take care of it. Mental health is very influential both physically and spiritually our body. Therefore, researchers conducted research related to the Implementation of Humanistic Theory in Improving Mental Health which has the aim of describing the implementation of humanistic theory in improving mental health so that readers and the public are able to know how important mental health is for us and how the implementation of humanistic theory can improve mental health. In this study, the method used is descriptive qualitative by means of library research, researchers seek and collect data from various literature sources, such as data sources from media coverage, books, journals, scientific articles. The purpose of the literature research itself is to review based on previous research sources that are relevant and in accordance with the discussion that will be reviewed by future researchers as the basis for reference data.